ADHD and The Deficit of Knowing: What? - Katie N Schenk (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2019)
This research-based essay explores the author’s experience with ADHD, as the essay’s formatting and usage of space evolves into a visual representation of the ADHD mind and questions the human capacity to identify, label, and differentiate inaccessible experiences. The common, often misinformed understanding of ADHD is disputed through in depth analyses of various brain functions. In particular, the atypical development of the executive functions housed in the ADHD person’s frontal lobe are explored through both contemporary research and personal experience, which are variously compared and contrasted to the supposed neurotypical experience. Consideration of ADHD’s lifelong stigma emphasizes the emotional components of the disorder that rarely receive attention, despite being equally integral to the disorder as any other attentional or behavioral components. Various theorists and theories of literature are invoked in order to create a dialogue within the essay concerned with the acquisition of knowledge and the impossibility of certainty, which merges into the main narrative at the end to contemplate self-acceptance.
Keywords: ADHD; executive functions; brain development; mental health; childhood disorders; rejection sensitivity dysphoria; RSD; Theory of mind